Engineering Innovation of a Length of Nearly 3300m large Diameter Pipeline Installed by HDD (2016)
The Yangtze River Crossing Project, which is part of the Chinese gas pipeline trunk network and aims to transmit the natural gas to the Yangtze River Delta area, sets up a record for the length of Horizontal Directional Drilling (HDD) in the world. The term of pipeline installed is 3300m, and the diameter is 40in. Many technical difficulties have been inevitably encountered in a large diameter hole reaming in fine sand, the calculation of section scour depth which determines the minimum buried depth of the pipe, protection of outside coating and the method of long distance pilot hole drilling, such other challenges. In view of this, it was recommended that two pipelines of 711mm should be installed to replace the existing one of 1016mm in diameter and 1% flooding scour depth obtained by reliable statistical analysis. In period of installation, application glass fiber reinforced epoxy resin as a protective coating, executing the pilot hole by Intersect Method. As a result, this super project is finished successfully on May 21.2013. The experience can be applied to any pipeline engineering the installed by horizontal directional drilling or similar works.